2019
DOI: 10.1186/s12906-019-2486-8
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive activity of petroleum ether fraction obtained from methanolic extract of Clinacanthus nutans leaves involves the activation of opioid receptors and NO-mediated/cGMP-independent pathway

Abstract: Background Methanol extract (MECN) of Clinacanthus nutans Lindau leaves (family Acanthaceae) demonstrated peripherally and centrally mediated antinociceptive activity via the modulation of opioid/NO-mediated, but cGMP-independent pathway. In the present study, MECN was sequentially partitioned to obtain petroleum ether extract of C. nutans (PECN), which was subjected to antinociceptive study with aims of establishing its antinociceptive potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Previous literatures have shown that in pain modulation, the opioid receptor is essential in the antinociceptive effect of many analgesic compounds. For instance, Zakaria et al 53 found out that petroleum ether extract of C. nutans exerted anti-nociceptive activity by activating opioid receptors and NO/cGMP pathway. Mehanna et al 54 investigated the anti-nociceptive effect of tadalafil in various pain models and revealed that the opioid receptors and NO/cGMP pathway were involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literatures have shown that in pain modulation, the opioid receptor is essential in the antinociceptive effect of many analgesic compounds. For instance, Zakaria et al 53 found out that petroleum ether extract of C. nutans exerted anti-nociceptive activity by activating opioid receptors and NO/cGMP pathway. Mehanna et al 54 investigated the anti-nociceptive effect of tadalafil in various pain models and revealed that the opioid receptors and NO/cGMP pathway were involved.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zakaria et al . 53 found out that petroleum ether extract of C. nutans exerted anti-nociceptive activity by activating opioid receptors and NO/cGMP pathway. Mehanna et al .…”
Section: Discussionmentioning
confidence: 99%
“…30 Another well-known model of thermal nociception, the hot-plate test was employed to check on the possible involvement of spinal, supraspinal pathways, and μ-opiate receptor agonists in regulation (CNS modulation) of pain response. 31 Both hot plate and tail immersion tests are extensively used for evaluating central anti-nociceptive activities. Opioid agents display their analgesic effects both via supra-spinal and spinal receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of MECN was described in detail in our previous published study [9] while the procedures involved in the preparation of semipurified petroleum ether partition were described in detail by Zakaria et al [11].…”
Section: Methodsmentioning
confidence: 99%
“…The HPLC analysis was conducted at the Laboratory of Phytomedicine, Forest Research Institute of Malaysia, Kepong, Malaysia, according to the protocols described by Mahmood et al [14] but with slight modifications. The exact procedures were described in detail by Zakaria et al [11].…”
Section: Methodsmentioning
confidence: 99%